Montmorillonite K-10 catalyzed Mannich reaction: Synthesis of aminonaphthoquinone derivatives from Lawsone. Issue 14 (18th July 2018) - Jayashree, Sankaranarayanan; Shivashankar, Kalegowda
Abstract: An efficient one-pot protocol for the synthesis of 2-((substituted amino)(4-phenyl)methyl)-3-hydroxy-naphthalene-1, 4-dione derivatives has been developed by the three-component reaction of 2-hydroxy-naphthalene-1, 4-dione, aromatic aldehydes and anilines/heterocyclic amines using montmorillonite K-10 as a catalyst. The advantages of this method include short reaction time, excellent yield and easy work-up. Graphical Abstract: